Trichomonas vaginalis PREVALENCE AND RISK FACTORS FOR WOMEN IN SOUTHERN BRAZIL - Cíntia Lima AMBROZIO; Andréia Saggin NAGEL; Sabrina JESKE; Guilherme Cassão Marques BRAGANÇA; Sibele BORSUK; Marcos Marreiro VILLELA (Revista do Instituto de Medicina Tropical de São Paulo)
SUMMARY Trichomonas vaginalis infections have been associated with other diseases so that epidemiological studies of the parasite are important and help to prevent the spread of the disease. This study aimed to determine the prevalence of T. vaginalis in female patients of 19 counties in southwestern Rio Grande do Sul, Brazil. For diagnosis, was used direct examination, followed by applying a socio-epidemiological questionnaire. We analyzed 300 women and 9% were infected by Trichomonas vaginalis. The highest frequency occurred in women between 18 and 39 years old, single/divorced/widowed, whose family income was at one minimum wage or less, and they had not completed the primary school. Statistically significant risk factors were: women reporting two or more sexual partners in the last year were 3.3 times more likely to acquire the parasite, and those in use of oral contraceptives were 2.7 times more likely to have T. vaginalis. Importantly, 33% of the asymptomatic women were infected, and most of the negative results were from women presenting symptoms consistent with the infection. The findings emphasize that it is necessary to expand the knowledge of individuals about the disease, especially among women with the above mentioned risk factors and also to include the regular screening of Trichomonas vaginalis infections in health centers.